2019
DOI: 10.3390/microorganisms7060177
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Metabolic Capabilities of Bacteria in the Mycobacterium tuberculosis Complex

Abstract: Pathogenic mycobacteria are known for their ability to maintain persistent infections in various mammals. The canonical pathogen in this genus is Mycobacterium tuberculosis and this bacterium is particularly successful at surviving and replicating within macrophages. Here, we will highlight the metabolic processes that M. tuberculosis employs during infection in macrophages and compare these findings with what is understood for other pathogens in the M. tuberculosis complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 189 publications
0
22
0
3
Order By: Relevance
“…Recent evidence also demonstrated the importance of this metabolic pathway in virulence and pathogenesis of mycobacteria 23 27 . Cholesterol was found to be utilised by MTB for not only the energy production and gluconeogenesis, but also for the biosynthesis of lipid virulent factors, such as phthiocerol-dimycocerosate (PDIM) and sulfolipids (SLs) 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence also demonstrated the importance of this metabolic pathway in virulence and pathogenesis of mycobacteria 23 27 . Cholesterol was found to be utilised by MTB for not only the energy production and gluconeogenesis, but also for the biosynthesis of lipid virulent factors, such as phthiocerol-dimycocerosate (PDIM) and sulfolipids (SLs) 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol is a preferred substrate for energy production and glucogenesis by MTB 14 . Recent studies also showed the codependency of cholesterol and fatty acid metabolism for the synthesis of virulence lipids 28 . Cholesterol degradation results in the production of excess propionyl-CoA, a compound required for biosynthesis of various virulence lipids, including PDIM, and SLs 40 .…”
Section: Discussionmentioning
confidence: 99%
“…While active Mtb requires carbohydrates as the main carbon source, Mtb in a latent phase that resides within the macrophage phagolysosome, where oxygen and nutrient depletion induce a massive metabolic rearrangement [ 132 ]. Notably, several analyses of Mtb transcriptional profiles from macrophages in vitro and from the lungs of mice and humans revealed a decreased glycolysis in concert with the upregulation of Mtb genes involved in lipids catabolism, proving that fatty acid ß-oxidation, gluconeogenesis, and cholesterol are the primary carbon and energy sources during infection in macrophages [ 133 ]. Despite the importance of CCM enzymes for promoting or maintaining a persistent infection, the presence of orthologous host enzymes could prevent the election of Mtb enzymes as potential drug targets.…”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…Mtb as any other bacterium is dependent on nitrogen uptake to synthesize vital biomolecules. However, Mtb has been found to prefer proteinogenic aa as the source of nitrogen over ammonium chloride when cultured in vitro [67,68]. Therefore, if the appropriate mechanisms and enzymes involved in these metabolic pathways were identified, the use of aa derived prodrugs could 'trick' Mtb to cleave off the aa and at the same time release the active form of the drug inside the cell.…”
Section: Discussionmentioning
confidence: 99%